2005
DOI: 10.1007/s10755-005-2863-8
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Racial Friendships and Social Distance Between Racial Groups on a College Campus

Abstract: This study examined the effectiveness of curriculum-focused diversity initiatives on a college campus by determining the relationships between GPA, social class, year in school, residential status, racial diversity courses taken, and cross-racial friendships on the level of social distance between Whites-Blacks, Whites-Hispanics, Hispanics-Whites, Hispanics-Blacks, Blacks-Whites, and Blacks-Hispanics. The data suggest that, while the institution does a good job of bringing diverse groups of students to the cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…Universities are substantially more diverse than primary and secondary schools, but diversity alone does not guarantee the development of meaningful social relationships across racial/ethnic boundaries [40,47]. Much of the existing research finds that, on college campuses, micro-level segregation is high, and that White students have the most segregated friendship networks [40,48]. Proximal diversity appears to lead to significant improvements in Latino/a-White interpersonal relationships, but has little effect on Black-White interpersonal relationships [49].…”
Section: Discussionmentioning
confidence: 99%
“…Universities are substantially more diverse than primary and secondary schools, but diversity alone does not guarantee the development of meaningful social relationships across racial/ethnic boundaries [40,47]. Much of the existing research finds that, on college campuses, micro-level segregation is high, and that White students have the most segregated friendship networks [40,48]. Proximal diversity appears to lead to significant improvements in Latino/a-White interpersonal relationships, but has little effect on Black-White interpersonal relationships [49].…”
Section: Discussionmentioning
confidence: 99%
“…Hamm et al (2005) and Quillian and Campbell (2003) observed that crossracial friendships tended to form with more frequency between American whites, Asians and Hispanics than among whites and blacks. Research also indicates that the deeper the skin tone of an African American, the less likely he or she is to be selected as a friend by a white American (Hamm et al 2005;Odell et al 2005;Quillian and Campbell 2003). This pattern of interaction has been observed even in groups with high racial diversity.…”
Section: Dynamics and Challenges Of Cross-racial Friendshipsmentioning
confidence: 97%
“…While racism and segregation have long been outlawed by civil rights legislation both in the USA and South Africa, as well as other countries, evidence of discrimination and racial disparity continues to exist (Gaertner and Dovidio 2005;Odell et al 2005;Xaba 2001). In the USA, literature on adolescents' cross-racial friendships shows that racial distinctions still exist in the choices individuals make regarding whom to befriend (Hamm et al 2005;Kao and Vaquera 2006;Scott 2004).…”
Section: Dynamics and Challenges Of Cross-racial Friendshipsmentioning
confidence: 99%
See 2 more Smart Citations